Acute Hypotensive, Diuretic and Antioxidant Activities Induced by Urtica circularis - Rodriguez Basso, A. (2016)
Aims: The aim of this study was to investigate the possible hypotensive and diuretic effects of ethanolic extract of Urtica circularis (Hicken) Sorarú (Urticaceae) using preclinical methods. Place and Duration of Study: Department of Pharmacology, School of Pharmacy and Biochemistry, Universidad de Buenos Aires, from July 2015 to January 2016. Methodology: Effect on blood pressure and heart rate on anaesthetized normotensive and hypertensive rats were measured using Statham Gould P23ID pressure transducer coupled to a Grass 79D polygraph. Rats were placed in metabolic cages in order to collect urine. Urinary volume was measured and sodium and potassium concentration was estimated from each urine sample using indirect ion-selective electrode potentiometry. The vasorelaxant activity of major compound was studied using isolated aortic rings. Antioxidant activity was estimated measuring 2,2 diphenyl 2 picryl hydrazyl hydrate radical scavenging activity. Results: The intravenous administration of the extract of U. circularis (0.1–30 mg/kg) in anaesthetized normotensive and hypertensive rats caused a dose-dependent reduction in the mean arterial pressure without affecting the heart rate. The greater reduction of blood pressure induced by U. circularis was observed in hypertensive rats (30 mg/kg: Spontaneously Hypertensive Rat: -34.7±3.3 mmHg, Spague Dawley: -18.3±3.9 mmHg). Cumulative urinary excretions 24 h after treatment with the extract 100 and 300 mg/kg were 18.2±1.2 and 14.9±1.5 mL respectively, significantly higher than the control group (9.0±1.3 mL). The addition of cumulative concentrations of vicenin-2 (10-7-10-4M) generated relaxation in endothelium-intact aortic rings pre-contracted with 10–7M Phenylephrine (Emax = 66.2±3.5%). Extract showed antioxidant activity reaching 45% of DPPH scavenging activity at 1000 μg/mL, meanwhile the flavonoid reached 20% of scavenger capacity. Conclusion: U. circularis, has a diuretic, antioxidant and hypotensive effect. Vicenin-2, the major component of this extract showed vasorelaxant activity, potentially responsible for the properties of the extract.